28GHz multiple input multiple output planar antenna for 5G mobile communication - An, Dong (2018)
v ABSTRACT Fifth generation (5G) is the next major phase of mobile telecommunications standards beyond the current 4G, which will operate at millimeter-wave frequency band. This thesis presents designs for MIMO planar antennas (single element and arrays at 28 GHz) Based on the best optimized single element patch, antenna array is designed at 28 GHz. An array theoretically offers higher gain compared to single antenna and offers more directive beam. The planar antennas are designed on Rogers RT Duroid with permittivity of 2.2 and the thickness of 0.381 mm. All structures are simulated and optimized using CST software. The performance are analyzed by means of the S parameters and the radiation pattern of the planar antenna. For single element antenna, are well matched at 28 GHz with S11 of -25.54 db in inset feed, and with S11 of -13.53 db in aperture coupled feed. The gain of single element antenna using inset feed is 7.721 db, while the gain of single element antenna using aperture coupled feed is 7.084 db. For 2x1 elements MIMO antenna using different two feeding techniques. The antenna is well matched at 28 GHz with S11 of -17.69 db, S21 of -34.78 db in inset feed, and with S11 of -17.3 db, S21 of -39.03 db in aperture coupled feed. The gain of single element antenna using inset feed is 8.169 db, while the gain of single element antenna using aperture coupled feed is 7.899 db. For 2x2 elements antenna array using aperture coupled feeding techniques. The antenna is well matched at 28 GHz with S11 of -10.2 db. The gain of 2x2 elements MIMO antenna using aperture coupled feed is 10.16 db.